Meningkatkan Motivasi Belajar Siswa di SDN Cilampang melalui Media Pembelajaran Digital dan Konvensional - Rakhman, Patra Aghtiar; Salsyabila, Annisa; Nuramalia, Nasywa; Gustiani, Putri Engelia (PGRI Kota Semarang, 2024)
This inquire about examines the viability of computerized and routine learning media in moving forward students' scholarly execution at SDN Cilampang. The most objective is to distinguish expanding understudy learning inspiration at Cilampang Basic School through advanced and customary learning media. This inquire about employments a subjective approach with writing ponder. This strategy gives a comprehensive understanding of how each sort of media impacts learning. Investigate discoveries uncover that advanced learning media altogether progresses understudy learning accomplishment compared to routine media. Understudies who utilize computerized apparatuses illustrate higher levels of engagement and way better scholastic results, as these instruments encourage intuitively learning encounters. Be that as it may, executing computerized media requires a more noteworthy speculation of time, assets and preparing for teachers. On the other hand, in spite of the fact that ordinary media, such as course readings and printed materials, are simpler to get to and apply, they have been demonstrated to be less viable in making strides understudy learning results. In this manner, it is prescribed that instructors at SDN Cilampang take a mixed approach, specifically by joining computerized and routine media. This combined methodology points to tackle the qualities of each sort of learning, assembly assorted learning needs and eventually optimizing instructive adequacy over classes.